Mutinies for equality : contemporary developments in law and gender in India - Herklotz, Tanja; De Souza, Siddharth Peter (Cambridge : Cambridge University Press, 2021)
Mutinies for Equality studies recent transformations in the area of law and gender in modern India. It tackles legal and social developments with regard to family life, sexuality, motherhood, surrogacy, erotic labour, sexual harassment in the workplace and violence against women, among others. It analyses reform efforts towards women's rights and LGBTIQ rights and attempts to situate where a reform has taken place, by whom it was brought about, and what impact it has had on society. It engages with protagonists who shape the debate around law and gender and locates their efforts into a socio-political context, thereby showing that the discourses around law and gender are closely connected to broader debates around legal pluralism, secularism and religion, identity, culture, nationalism, and family. The book offers compelling evidence that the drivers of change are emerging from beyond the traditional institutions of courts and parliament, and that to understand the everyday implications of legal reforms, it is important to look beyond these institutional sources.
Family matters, gender matters : courts on the rule against restraints on alienation / Krithika Ashok -- Missing women in the Indian judiciary : the inadequacies of the judicial appointment process / Siddharth Peter de Souza and Medha Srivastava-Kehrer -- Is the Supreme Court cherry-picking its gender battles? / Jayna Kothari -- Juxtaposing equality? : Muslim women's rights in the normative realm of secularism and personal law in India / Katharina Wommelsdorff -- Is sexuality anti-Indian? : reflections on obscenity in contemporary Indian popular discourse / Fritzi-Marie Titzmann -- Armed with the constitution : feminist litigation on Indian family law / Tanja Herklotz -- Nikah Halala : the petition, the promise, and the politics of personal law / Saumya Saxena -- The politics of erotic labour : a case study of Mumbai bar dancers / Sameena Dalwai -- Reactionary executive versus deliberative legislature : the case of how the legislature championed compensation for reproductive labour while regulating surrogacy / Mandira Kala -- Interrogating the freedoms of queer liberation in India / Jason Keith Fernandes -- The politics of regulating adult sexuality through the institution of marriage : reflections on queer experiences from India / Sourav Mandal -- Conditions of possibility : law, patriarchy, and single motherhood in India / Saptarshi Mandal -- Turning to the state : between processing disputes and protecting autonomy / Kalindi Kokal -- Towards an egalitarian workplace : developments in anti-sexual harassment law / Poornima Hatti and Aparna Ravi.
Title from publisher's bibliographic system (viewed on 11 Jun 2021).
Keywords: Sex discrimination against women -- Law and legislation -- India; Equality before the law -- India; Women's rights -- India; Women -- Legal status, laws, etc; Sexual harassment of women -- Law and legislation -- India